Particle Swarm Optimised Controller for Solid-State Transfer Switch Towards Fast Power Transfer and PQ Mitigation - Sebastian G.; Hannan M.A.; Al-Shetwi A.Q.; Ker P.J.; Muttaqi K.M.; Uddin M.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Controllers; Energy transfer; Errors; Fuzzy logic; Harmonic analysis; Particle swarm optimization (PSO); Power quality; Fitness functions; Fuzzy logic controllers; Harmonic elimination; Nonlinear load; Optimisations; Particle swarm; Power transfers; Solid-state transfer switches; Swarm optimization; Transfer time; Membership functions